2016
DOI: 10.4040/jkan.2016.46.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effects of a Cognitive-behavioral Therapy Based Program in Reducing Internalized Stigma in Patients with Schizophrenia

Abstract: Purpose: This study was done to develop a internalized stigma reducing program based on cognitive-behavioral therapy and appropriate for patients with schizophrenia and to evaluate its effectiveness. Methods: The study design was a mixed method research. Qualitative study, 13 patients with schizophrenia who had experience in overcoming stigma were purposively chosen for interviews and data were analyzed using Giorgi method. Quantitative study, 64 patients with schizophrenia (experimental group =32, control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The personal and internal stress factors experienced by people with schizophrenia in the community include side-effects caused by antipsychotic drugs, other health problems [6], psychotic symptoms such as hallucinations and delusions of persecution, and reduced quality of life and wellbeing due to frequent cycles of hospitalization and discharge [7]. Furthermore, people with schizophrenia experience discrimination in their daily life, as well as a high level of stress from social prejudice and stigma [8]. Psychosocial rehabilitation therapy and drug therapy have been provided to people with schizophrenia to reduce their stress, control symptoms, and restore function [9].…”
Section: Introductionmentioning
confidence: 99%
“…The personal and internal stress factors experienced by people with schizophrenia in the community include side-effects caused by antipsychotic drugs, other health problems [6], psychotic symptoms such as hallucinations and delusions of persecution, and reduced quality of life and wellbeing due to frequent cycles of hospitalization and discharge [7]. Furthermore, people with schizophrenia experience discrimination in their daily life, as well as a high level of stress from social prejudice and stigma [8]. Psychosocial rehabilitation therapy and drug therapy have been provided to people with schizophrenia to reduce their stress, control symptoms, and restore function [9].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, infertility-related stress can be characterized by identity crises or loss of identity as a woman and potential parent, interrelational strain, perceived social isolation and stigma, anxiety, depression, and reduced self-esteem (Woods et al, 2022). As reported in previous studies, CBT not only has shown benefits for emotional distress, such as anxiety and depression (Abdollahi et al, 2018;Sexton et al, 2010) but also has a positive effect on reducing stigma (Kim & Jun, 2016), as well as improving self-esteem (Domar et al, 2000).…”
Section: Discussionmentioning
confidence: 91%